2018
DOI: 10.1111/pbr.12616
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific compatibility barriers, development of interspecific hybrids through embryo rescue and lineage ofTrifolium alexandrinum(Egyptian clover)—important tropical forage legume

Abstract: Genetic improvement of Trifolium alexandrinum L. is hampered because of narrow genetic base and lack of interspecies compatibility information. The study was envisaged to understand the interspecies incompatibility and the affinity between T. alexandrinum and 22 species of the genus representing different sections and to develop interspecific crosses. Development of interspecific hybrids with T. resupinatum, T. lappaceum, T. subterraneum, T. vesiculosum and T. echinatum, through embryo rescue, revealed their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
1
4
1
Order By: Relevance
“…The genus Trifolium has been divided in eight sections [1]. In the present study, clustering of T. subterraneum belonging to section Trichocephalum of the genus, with T. alexandrinum and T. salmoneum of section Trifolium, indicated that the three species possessed relatedness which was congruent with earlier reports [3] [16] [17] [18] [19]. In fact, Lotoidea is the largest section and has served as source taxa for the evolution of many other sections [1].…”
Section: Genetic Relationship Among Accessionssupporting
confidence: 91%
“…The genus Trifolium has been divided in eight sections [1]. In the present study, clustering of T. subterraneum belonging to section Trichocephalum of the genus, with T. alexandrinum and T. salmoneum of section Trifolium, indicated that the three species possessed relatedness which was congruent with earlier reports [3] [16] [17] [18] [19]. In fact, Lotoidea is the largest section and has served as source taxa for the evolution of many other sections [1].…”
Section: Genetic Relationship Among Accessionssupporting
confidence: 91%
“…Generalist bee species including honeybees, bumblebees and solitary bees are common pollinators of Trifolium (Rao & Stephen, 2009;Zohary & Heller, 1984). Heterospecific pollen transfer is often costly due to post-pollination and postzygotic barriers (Malaviya et al, 2018;Repkova et al, 2006;Roy et al, 2011). While we could not find data quantifying the strength of reproductive isolation in any of the specific species pairs in our study, surveys across the genus suggest that intrinsic barriers in interspecific crosses are substantial and widespread (Abberton, 2007), and hybrids are extremely rare in nature (Zohary & Heller, 1984).…”
Section: Study Systemcontrasting
confidence: 57%
“…More recently, Marshall et al (2008) showed that introgression of reproductive traits from T. nigrescens to T. repens increased the seed yield. Malaviya et al (2018) investigated the interspecies incompatibility and affinity between T. alexandrinum and 22 Trifolium species. Although there was incompatibility among most of the crosses, embryo rescue and intensive crossing produced successful hybrids.…”
Section: Past Successes Of Using Germplasm In Forage Breedingmentioning
confidence: 99%